Intraoperative marking of pulmonary nodules in a hybrid operating room: electromagnetic navigation bronchoscopy versus percutaneous marking - Gómez-Hernández, María Teresa; Rivas Duarte, Cristina E.; Fernández García-Hierro, José María; Fuentes, Marta G.; Colmenares, Oscar; Forcada Barreda, Clara; Gómez Valle, Francisco; Jiménez García, Irene; Jiménez, Marcelo F. (Frontiers in Surgery, 2024)
BackgroundIntraoperative identification of subsolid or small pulmonary nodules during minimally invasive procedures is challenging. Recent localization techniques show varying success and complications. Hybrid operating rooms (HORs), equipped with radiological tools, facilitate intraoperative imaging. This study compares the accuracy and safety of marking pulmonary nodules using electromagnetic navigation bronchoscopy (ENB) combined with Cone Beam Computed Tomography (CBCT) vs. CBCT-guided percutaneous marking (PM).MethodsThis retrospective cohort study included patients with pulmonary nodules scheduled for minimally invasive resection in a HOR. Marking techniques included ENB assisted by CBCT and PM guided by CBCT. The study compared the success rate, procedure time, intraoperative complications and radiation dose of both techniques.ResultsA total of 104 patients with 114 nodules were included (October 2021—July 2024). Thirty nodules were marked using ENB, and 84 with PM. One case used both techniques due to ENB failure. No differences among groups were found in nodule characteristics. Success rates were similar (93.3% in ENB group vs. 91.7% in PM group, p = 1). Marking took significantly longer time in the ENB group (median 40 min) compared to PM group (25 min, p = 0.007). Five (6%) patients in the PM group experienced intraoperative complications compared to none in the ENB (p = 0.323). Radiation dose was significantly higher in the ENB group (p = 0.002).ConclusionsENB assisted by CBCT is a safe and effective technique, with success rates comparable to CBCT-guided PM, though it may result in longer procedural times and higher radiation doses.